TOÀN CẦU HÓA TÔN GIÁO VÀ SỰ PHÁT TRIỂN CỦA ĐẠO TIN LÀNH Ở TÂY NGUYÊN - Mai, Minh Nhật (Trường Đại học Đà Lạt, 2023)
This article illustrates the concept, characteristics and operation of religious globalisation. We focus on the proliferation of Protestantism in the Central Highlands of Vietnam, under the influence of religious globalisation, from the last decades of the 20th Century to the early 21st Century.